Problematika Final dan Mengikat Putusan Arbitrase dalam Undang-Undang Nomor 30 Tahun 1999 - Hizkia Raymond (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
In modern law the emergence of several settlements of a dispute outside the judiciary. One of them is the practice of arbitration, which is becoming known as a dispute resolution outside the Court, especially on business issues. The development of the form of business in Indonesia, brings other consequences for the business itself, namely the hope to be able to resolve any disputes that may arise, quickly, cheaply and in the best possible way. The implementation of Law 30 of 1999 has become the latest legal basis for dispute resolution and arbitration in Indonesia. The object of research taken in this study is only regarding arbitration in the law. What is of concern is the low legal force of the final and binding arbitration award which is the background for holding the arbitration. An example is clearly stated in article 72, where in the explanation expressis verbis explains the problem of the arbitral award. In conducting this research, the author uses a normative juridical research method, using a literature study. The results of this study indicate that there are problems in the law, especially in the final and binding diction. The suggestions that can be proposed to the authorized institution are to immediately issue rules or guidelines for the solution of these problems.